A hazel tree relict community (Corylus avellana L., Betulaceae) from the Guadiana River Middle Basin (Ciudad Real, Spain) - Luengo Nicolau, Enrique; Sánchez-Mata, Daniel (Lazaroa, 2015)
A new community is proposed for the checklist of Iberian Peninsula vegetation: Chamaeirido foetidissimae-Coryletum avellanae. This forest vegetation type was discovered in the riparian landscapes along the Middle Basin of the Guadiana River (Ciudad Real, Spain), and has a true relict character. These hazel tree relict formations are seriously threatened by human activities in the study area.